2015 IEEE Jordan Conference on Applied Electrical Engineering and Computing Technologies (AEECT) 2015
DOI: 10.1109/aeect.2015.7360563
|View full text |Cite
|
Sign up to set email alerts
|

Detection of water leakage in buried pipes using infrared technology; A comparative study of using high and low resolution infrared cameras for evaluating distant remote detection

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 9 publications
1
28
0
2
Order By: Relevance
“…The first natural frequency of the bridge as calculated from displacements obtained with vision-based technologies was in a good match to the frequency calculated from GNSS (Yu et al, 2014). A comparative study between high resolution and low-cost infrared vision systems has shown that equally good results can be obtained when considering appropriate analysis algorithms suggesting that with high resolution output even better results could be obtained (Shakmak and Al-Habaibeh, 2015). The studies of applications of smartphone technologies in long-term monitoring projects are not yet reported.…”
Section: Introductionmentioning
confidence: 66%
“…The first natural frequency of the bridge as calculated from displacements obtained with vision-based technologies was in a good match to the frequency calculated from GNSS (Yu et al, 2014). A comparative study between high resolution and low-cost infrared vision systems has shown that equally good results can be obtained when considering appropriate analysis algorithms suggesting that with high resolution output even better results could be obtained (Shakmak and Al-Habaibeh, 2015). The studies of applications of smartphone technologies in long-term monitoring projects are not yet reported.…”
Section: Introductionmentioning
confidence: 66%
“…The basic function of thermography cameras is illustrated in Figure 5. Since changes in temperature measurements are one of the common indications of gas discharge in the pipelines surrounding as gas leaks usually cause abnormal temperature distribution, therefore, using IRT for pipeline monitoring become widely accepted due to its capability to measure temperature changes in real-time and in a non-contact manner [76,77]. IRT as a contactless and non-invasive condition monitoring tool is also applicable for various condition monitoring applications such as heat transfer [78], tensile failure [79], concrete and masonry bridges [80].…”
Section: Exterior Based Leak Detection Methodsmentioning
confidence: 99%
“…A high-resolution IR image of a surface above a simulated underground leakage and the associated temperature profiles [3].…”
Section: Figurementioning
confidence: 99%
“…thermographic devices that detect infrared radiation of bodies, rely on the change in the temperature of the surface above water leaked which rises by capillarity through the subsurface [3]. Fig.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation